Possible link between large artery stiffness and coronary flow velocity reserve. Issue 6 (18th October 2007) - Saito, M; Okayama, H; Nishimura, K; Ogimoto, A; Ohtsuka, T; Inoue, K; Hiasa, G; Sumimoto, T; Higaki, J
Abstract : Background: Population studies have shown that increased large artery stiffness is an independent predictor of cardiovascular events. Experimental studies have shown that a stiff aorta is associated with decreased coronary blood flow. However, a link between large artery stiffness and coronary microvascular function in the clinical setting has not been demonstrated previously. Objective: To evaluate the relationship between large artery stiffness and coronary flow velocity reserve (CFVR). Patients and methods: 102 consecutive subjects (mean (SD) age 62 (10) years) without coronary and peripheral arterial disease were enrolled in the study. After 15 minutes' rest, measurements were obtained of brachial-ankle pulse wave velocity (baPWV), augmentation index (AIx) from a carotid pulse tracing, and transthoracic echocardiographic measures, including coronary flow velocity in the left anterior descending coronary artery. In addition, coronary flow velocity during hyperaemia was measured during an intravenous infusion of adenosine triphosphate. CFVR was defined as the ratio of hyperaemic to basal coronary velocity. Results: Subjects with decreased CFVR (<2.5; n = 40) had significantly higher baPWV (1848 (369) cm/s vs 1548 (333) cm/s; p<0.001), greater AIx (25.3 (11.0)% vs 16.3 (20.0)%; p = 0.01) and greater pulse pressure (PP) (64 (13) mm Hg vs 54 (13) mm Hg; p<0.001) than those with normal CFVR (⩾2.5; n = 62). Multivariate analysis showed that AIx and PP were independent predictors of CFVR ( r = −0.32, p<0.001 and −0.25, p = 0.02, respectively). Conclusions: The data suggest that large artery stiffening is linked to a reduction of CFVR, which may partially explain the higher cardiac event rate in patients with increased large artery stiffness.